Dendritic growth of protein gel in the course of sweat pore plugging by aluminium salts under physiological conditions. Issue 35 (25th August 2021) - Galey, Jean-Baptiste; Botet, Robert; Sakhawoth, Yasine; Dupire, Jules; Leonforte, Fabien; Chardon, Marion; Monti, Fabrice; Tabeling, Patrick; Cabane, Bernard
Abstract : Confocal microscopy + numerical simulations reveal the mechanisms involved in the formation of a dendritic plug appearing in sweat flowing across a microfluidic channel in the presence of aluminium salts. Abstract : Are aluminium ions unavoidable in antiperspirants? To answer this question, we present confocal microscopy images of dendritic plugs appearing in sweat flowing across a microfluidic channel in the presence of aluminium salts. By comparing with numerical simulations, we identify the mechanisms forming this structured protein gel inside the pore.